Utility of the Modified Isolated-check Visual Evoked Potential Technique in Functional Glaucoma Assessment. Issue 4 (April 2020) - Kolomeyer, Natasha N.; Drinkwater, Owen J.; Drivas, Eleni; Zakik, Amir; Zemon, Vance; Sidoti, Paul A.; Tsai, James C.; Panarelli, Joseph F.
Abstract : Pre[Combining Acute Accent]cis: Cortical response to low-contrast stimuli, as measured by isolated-check visual evoked potential (icVEP) technology, has the potential to provide functional assessment that may complement standard achromatic perimetry in assessing glaucomatous change. Purpose: To evaluate the utility of modified icVEP testing in detecting functional glaucomatous damage. Materials and Methods: Subjects who met predetermined criteria of controls, glaucoma suspects, preperimetric glaucoma, or glaucoma were enrolled in this prospective cross-sectional study from a single tertiary care center. Glaucoma patients were further categorized as early, moderate, advanced, or severe on the basis of Hodapp-Anderson-Parrish criteria. icVEP testing was performed with ten 2-second runs per qualified eye using the EvokeDx testing software. Multivariate statistics were used to calculate signal-to-noise ratios (SNR) and perform outlier analysis. Results: In total, 140 eyes met criteria (mean±SD; age of 63±14 y; 49% male; logMAR visual acuity, 0.11±0.089). There was no significant difference in age, sex, or logMAR visual acuity among the groups. Controls had a significantly higher SNR than all other groups ( P <0.003), including patients with preperimetric glaucoma. Among those with glaucoma, the early glaucoma patients had significantly higher SNR than the moderate, advanced, or severe glaucoma cohorts ( P <0.04). The optimal SNR cutoff for differentiating between glaucomatous and nonglaucomatous eyes was 0.95, both with (sensitivity 82%, specificity 76%) and without (sensitivity 82%, specificity 100%) glaucoma suspects included in analysis. Conclusions: icVEP technology has the potential to complement standard achromatic perimetry in functional assessment of glaucomatous defects.